SYNTHESIS OF METHYL MALATE THROUGH ESTERIFICATION REACTIONS USING METHANOL SOLVENTS AND INSITU REACTIONS WITH ACID CATALYSTS - Eci Endang Sinulingga; Daniel -; Chairul Saleh; Agustina Rahayu Magdaleni (JURNAL ATOMIK, 2020)
Research has been carried out on the synthesis of methyl malate through esterification reactions using methanol solvents and in situ reactions with acid catalysts. Esterification of malic acid was carried out with a ratio of methanol 1:3 to produce pale yellow methyl malate with a yield of 94.06%. The formed methyl malate then characterizes using the FT-IR instrument and tests its HLB value. The result of FT-IR analysis which will indicate that methyl malate has formed is that the carboxylic group from malic acid has been converted into an ester group from the esterification reaction. The wavenumber of the carboxylic group of malic acid is 1720.50 cm-1 and the ester group is the result of an esterification reaction at wave number 1735.93 cm-1, indicating that methyl malate has been formed. Furthermore, for the HLB value based on the results of the study obtained at 11.2, which indicates that methyl malate is included in the O / W emulsifier (Oil in Water).